Dearborn : stories - Zeineddine, Ghassan (Tin House, 2023)
"Spanning several decades, Ghassan Zeineddine's debut collection examines the diverse range and complexities of the Arab American community in Dearborn, Michigan. In ten tragicomic stories, Zeineddine explores themes of identity, generational conflicts, war trauma, migration, sexuality, queerness, home and belonging, and more. In Dearborn, a father teaches his son how to cheat the IRS and hide their cash earnings inside of frozen chickens. Tensions heighten within a close-knit group of couples when a mysterious man begins to frequent the local gym pool, dressed in Speedos printed with nostalgic images of Lebanon. And a failed stage actor attempts to drive a young Lebanese man with ambitions of becoming a Hollywood action hero to LA, but Immigration and Customs Enforcement agents have other plans. By turns wildly funny, incisive, and deeply moving, Dearborn introduces readers to an arresting new voice in contemporary fiction and invites us all to consider what it means to be part of a place and community, and how it is that we help one another survive"--